2021
DOI: 10.1101/2021.06.09.21257809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaccination history for diphtheria and tetanus is associated with less severe COVID-19

Abstract: Background: COVID-19 is characterized by strikingly large, mostly unexplained, interindividual variation in symptom severity. While some individuals remain nearly asymptomatic, others suffer from severe respiratory failure. It has been hypothesized that previous vaccinations for other pathogens, in particular tetanus, may provide protection against severe COVID-19. Methods: We made use of data on COVID-19 testing from 103,049 participants of the UK Biobank (mean age 71.5 years, 54.2% female), coupled to immun… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(39 reference statements)
1
0
0
Order By: Relevance
“…Our propensity-weighted methodology allows us to isolate differences attributed to MMR and Tdap vaccination and revealed that severe disease outcomes (hospitalization, transfer to intensive care unit, or death) were reduced in MMR-or Tdap-vaccinated individuals by 32%-38% and 20%-23%, respectively. A recent study using the UK Biobank supports our finding that prior Tdap vaccination associates with reduced COVID-19 severity, 90 but only covaried for age, sex, respiratory disease diagnosis, and socioeconomic status, while our propensity scoring methodology adjusted for significantly more confounding variables. Our exploratory analyses suggest that the women were protected more than men by prior MMR and Tdap vaccination, and younger patients were protected more than older, which may reflect the role of gender on vaccination outcomes and the general decline in response to vaccines that occurs with aging.…”
Section: Ll Open Accesssupporting
confidence: 82%
“…Our propensity-weighted methodology allows us to isolate differences attributed to MMR and Tdap vaccination and revealed that severe disease outcomes (hospitalization, transfer to intensive care unit, or death) were reduced in MMR-or Tdap-vaccinated individuals by 32%-38% and 20%-23%, respectively. A recent study using the UK Biobank supports our finding that prior Tdap vaccination associates with reduced COVID-19 severity, 90 but only covaried for age, sex, respiratory disease diagnosis, and socioeconomic status, while our propensity scoring methodology adjusted for significantly more confounding variables. Our exploratory analyses suggest that the women were protected more than men by prior MMR and Tdap vaccination, and younger patients were protected more than older, which may reflect the role of gender on vaccination outcomes and the general decline in response to vaccines that occurs with aging.…”
Section: Ll Open Accesssupporting
confidence: 82%
“…Крім того, низька антигенна доза у вигляді АДП-м-анатоксину також вводиться у віці від 9 до 14 років. Тому цікавим і доцільним є вивчення особливостей перебігу інфекційних захворювань, в тому числі й COVID-19, залежно від рівня гуморального імунітету проти дифтерії [14,15].…”
Section: гуморальний імунітет проти дифтерії у дітей шкільного віку п...unclassified
“…. У світовому науковому товаристві з'являється інформація про те, що вакцинація проти деяких інфекцій може бути ефективною і проти SARS-CoV-2, а тому вакциновані від дифтерії чи правця мали меншу ймовірність розвитку тяжкого ступеня COVID-19, порівняно з невакцинованими [2,4]. Ці твердження ґрунтуються на вивченні спорідненості білків коронавірусу та деяких патогенних мікроорганізмів, зокрема, структура правцевого та дифтерійного токсинів схожа на білок SARS-CoV-2, тому введення дифтерійно-правцевого анатоксину може мати захисний ефект і проти SARS-CoV-2 [4].…”
unclassified